Keeping the circle : American Indian identity in eastern North Carolina, 1885-2004 - Oakley, Christopher Arris (Indians of the Southeast., 2005)
Keeping the Circle presents an overview of the modern history and identity of the Native peoples in twentieth-century North Carolina, including the Lumbees, the Tuscaroras, the Waccamaw Sioux, the Occaneechis, the Meherrins, the Haliwa-Saponis, and the Coharies. From the late 1800s until the 1930s, Native peoples in the eastern part of the state lived and farmed in small isolated communities. Although relatively insulated, they were acculturated, and few fit the traditional stereotype of an Indian. They spoke English, practiced Christianity, and in general lived and worked like other North Carolinians. Nonetheless, Indians in the state maintained a strong sense of "Indianness."